Retraction Notice: Transition in Dental Treatment Utilization in Jammu And Kashmir, India - A 10 Year Retrospective Study - Shah, Aasim Farooq; Batra, Manu; Ishrat, A. (Nepal Journal of Epidemiology, 2018)
RETRACTED ARTICLE: It was brought to the editorial notice, that this article has fabricated data. This was confirmed and Authors were communicated; they acknowledged and agreed that this has been done by mistake. To avoid misleading the scientific community the article was retracted on 30th September 2017 (DOI: http://dx.doi.org/10.3126/nje.v6i4.17257). Nepal J Epidemiol. 2017;7(3); 699